2022
DOI: 10.1186/s13020-022-00646-z
|View full text |Cite|
|
Sign up to set email alerts
|

Natural products: potential drugs for the treatment of renal fibrosis

Abstract: With the increasing prevalence and mortality, chronic kidney disease (CKD) has become a world public health problem. As the primary pathological manifestation in CKD, renal fibrosis is often used as a critical target for the treatment of CKD and inhibits the progression of CKD to end-stage renal disease (ESRD). As a potential drug, natural products have been confirmed to have the potential as a routine or supplementary therapy for chronic kidney disease, which may target renal fibrosis and act through various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The release experiment was conducted in parallel using three separate parts, each shaken at 37°C and 200 rpm. At specific time points (3,6,12,24,48,72, and 168 h), 0.2 mL of the release medium was sampled from each part. Subsequently, an equal volume of blank release medium preheated to 37°C was added to the respective parts.…”
Section: In Vitro Release Of Ua-ptx Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…The release experiment was conducted in parallel using three separate parts, each shaken at 37°C and 200 rpm. At specific time points (3,6,12,24,48,72, and 168 h), 0.2 mL of the release medium was sampled from each part. Subsequently, an equal volume of blank release medium preheated to 37°C was added to the respective parts.…”
Section: In Vitro Release Of Ua-ptx Npsmentioning
confidence: 99%
“…10 Numerous therapeutic effects in various diseases have been attributed to bioactive molecules derived from natural sources. [11][12][13][14] Continual reports have identified a significant number of natural bioactive molecules that exhibit inhibitory properties against P-gp. [15][16][17] These bioactive molecules are widely distributed in nature, offering a vast pool of resources for the efficient and non-toxic screening and exploration of P-gp inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported that the sentence below was missing in the article.…”
Section: Correction To: Chinese Medicine (2022) 17:98 Https...mentioning
confidence: 99%
“…In traditional medicine in the East and West, herbal prescriptions that are composed of several medicinal plants have been used to alleviate fibrotic diseases of the major organs, including the liver, kidneys, and lungs [11][12][13]. Interestingly, plant extracts with these effects contain several polyphenolic compounds in common, and studies on the pharmacological effects of these compounds are attracting attention [14][15][16]. A literature search by Alberti showed that plant extracts that contain hydroxycinnamic acids inhibited experimentally induced liver fibrosis [17].…”
Section: Introductionmentioning
confidence: 99%